Mapping the inner kpc of the interacting Seyfert galaxy NGC 2992: Stellar populations and gas kinematics. Issue Volume 15:Issue S359(2020) (March 2019) - Guolo-Pereira, Muryel; Ruschel-Dutra, Daniel
Abstract: We present Gemini Multi-Object Spectrograph Integral Field Unit (GMOS-IFU) observations of the inner 1.1 kpc of the interacting Seyfert galaxy NGC 2992. From full spectral synthesis we found that the stellar population is mainly (up to 80 per cent of the total light) composed by an old (t ≥ 1.4 Gyr) metal-rich ( Z ≥ 2.0) populations with a smaller but considerable contribution (up to 30 per cent) from young (t ≤ 100 Myr) metal-poor ( Z ≥ 1.0) populations. The gas kinematics presents two main components: one from gas in orbit in the galaxy disk and an outflow with mass outflow rate of ˜2 Mʘ yr –1 and a kinematic power of ˜ 2 × 10 40 erg s –1 .